(untitled) (Journal of Energy and Safety Technology (JEST), 2026)
Scenario completeness refers to the extent to which all credible process hazard scenarios have been identified and documented. Ensuring the completeness of process hazard scenarios is foundational to the quality and credibility of a Hazard and Operability (HAZOP) study. As the cornerstone of qualitative risk assessment in the process industry, HAZOP’s effectiveness depends on the systematic identification of all credible deviations and their associated hazardous consequences. This paper proposes hazard scenario completeness as a key result indicator for evaluating the quality of HAZOP studies, based on the recognition that omitted scenarios can significantly underestimate risk and compromise safeguard adequacy. A structured framework is presented for assessing scenario completeness, including benchmarking against established scenario taxonomies – such as API RP 14C – and analysing coverage through cause-consequence pairs. The approach emphasizes the role of historical data, expert knowledge, and consistency in the identification of representative and credible hazard scenarios across different process nodes. The findings suggest that incorporating scenario completeness as a quantifiable metric can enhance the reliability, traceability, and defensibility of HAZOP outputs. This approach offers a practical basis for both internal quality assurance and external regulatory validation of process hazard analyses.